2003
DOI: 10.1097/01.md.0000090401.56130.59
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Betel Quid Chewing as a Risk Factor for Cirrhosis

Abstract: Betel quid chewing, part of traditional Taiwanese culture, is common in 10%-20% of the human population worldwide. In this case-control study we assessed the independent and interactive role of habitual betel quid chewing and chronic hepatitis B virus (HBV) and hepatitis C virus (HCV) infection on risk of cirrhosis. Subjects enrolled included 210 pairs of sex- and age-matched cirrhotic patients and healthy controls. Information on risk factors was obtained through serologic examination of hepatitis B surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 58 publications
1
45
0
Order By: Relevance
“…Betel chewing is hepatotoxic and hepatocarcinogenic, owing to the high concentration of aflatoxin B1 in A. catechu nuts (8) , the high concentration of safrole in P. betle plants (4) and the specific carcinogenic nitrosamines formed from arecal alkaloids and bacterial nitrite products during betel chewing and after acidification of swallowed chew materials in the stomach (2) . Previous case-control and cohort studies have demonstrated positive associations between betel chewing, LC (3) and HCC (4)(5)(6) . However, hospital-based, age-and gender-matched case-control studies are liable to recall bias with possible overestimation of associations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Betel chewing is hepatotoxic and hepatocarcinogenic, owing to the high concentration of aflatoxin B1 in A. catechu nuts (8) , the high concentration of safrole in P. betle plants (4) and the specific carcinogenic nitrosamines formed from arecal alkaloids and bacterial nitrite products during betel chewing and after acidification of swallowed chew materials in the stomach (2) . Previous case-control and cohort studies have demonstrated positive associations between betel chewing, LC (3) and HCC (4)(5)(6) . However, hospital-based, age-and gender-matched case-control studies are liable to recall bias with possible overestimation of associations.…”
mentioning
confidence: 99%
“…Taiwan, with high prevalence rates of both cirrhosis and liver cancer, has an increasing rate of betel (Areca catechu) chewing; the nuts are chopped and, with Piper betle vine flower heads, used as betel-chews by a tenth of the 23 million inhabitants currently (2) . This habit is recognized to be carcinogenic in man (2) and has been reported to be associated with LC and with HCC in Taiwan (3)(4)(5)(6) .…”
mentioning
confidence: 99%
“…We designed a structured questionnaire, as described previously (Tsai et al, 2003), to obtain information on age, sex, habits of smoking (the quantity of cigarettes smoked per day and the duration of smoking), alcohol drinking (the quantity and duration of drinking, types of alcoholic beverage), and BQ chewing practice (the duration of habit, daily amount consumed, type of BQ consumed). A habitual BQ chewer was defined as chewing one quid or more daily for at least one year.…”
Section: Structured Questionnaire and Standardized Interviewmentioning
confidence: 99%
“…On the other hand, animals feeding BQ in the long term developed both chronic hepatocyte necroinflammation (Sarma et al, 1992) and liver cancer (Bhide et al, 1979;Nishikawa et al, 1992). Epidemiological data indicated that habitual BQ chewing is an independent risk factor for liver cirrhosis (Tsai et al, 2003;Hsiao et al, 2007). Cirrhosis itself is a preneoplastic lesion of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that use of betel nut/quid was associated with thiamine defi ciency, [22,23] aggravated effects of vitamin-D defi ciency, [24] and was associated with central obesity, hyperglycemia, diabetes mellitus, [13,25] cirrhosis, [26] and goiter. [27] Various studies have shown that betel nut use during pregnancy has adverse effect on birth outcomes, including low birth weight, shorter birth length, and preterm delivery.…”
Section: Introductionmentioning
confidence: 99%